The Mechanisms Underlying the Hypolipidaemic Effects of Grifola frondosa in the Liver of Rats - Ding, Yinrun; Xiao, Chun; Wu, Qingping; Xie, Yizhen; Li, Xiangmin; Hu, Huiping; Li, Liangqiu (Frontiers in Microbiology, 2016)
The present study investigated the hypolipidaemic effects of Grifola frondosa and its regulation mechanism involved in lipid metabolism in liver of rats fed a high-cholesterol diet. The body weights and serum lipid levels of control rats, of hyperlipidaemic rats, and of hyperlipidaemic rats treated with oral G. frondosa were determined. mRNA expression and concentration of key lipid metabolism enzymes were investigated. Serum cholesterol, triacylglycerol, and low-density lipoprotein cholesterol levels were markedly decreased in hyperlipidaemic rats treated with G. frondosa compared with untreated hyperlipidaemic rats. mRNA expression of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), acyl-coenzyme A: cholesterol acyltransferase (ACAT2), apolipoprotein B (ApoB), fatty acid synthase (FAS), and acetyl-CoA carboxylase (ACC1) were significantly down-regulated, while expression of cholesterol 7-alpha-hydroxylase (CYP7A1) was significantly up-regulated in the livers of treated rats compared with untreated hyperlipidaemic rats. The concentrations of these enzymes also paralleled the observed changes in mRNA expression. Two-dimensional polyacrylamide gel electrophoresis (2-DE) and Matrix-Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry (MALDI-TOF-MS) were used to identify 20 proteins differentially expressed in livers of rats treated with G. frondosa compared with untreated hyperlipidemic rats. Of these 20 proteins, seven proteins were down-regulated, and 13 proteins were up-regulated. These findings indicate that the hypolipidaemic effects of G. frondosa reflected its modulation of key enzymes involved in cholesterol and triacylglycerol biosynthesis, absorption, and catabolic pathways. G. frondosa may exert anti-atherosclerotic effects by inhibiting LDL oxidation through down-regulation and up-regulating proteins expression in the liver of rats. Therefore, G. frondosa may produce both hypolipidaemic and anti-atherosclerotic effects, and potentially be of use as a functional food for the treatment or prevention of hyperlipidaemia and atherosclerosis.